2021
DOI: 10.1088/1757-899x/1163/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation of Austenitic Stainless Steel at High Temperature in Simulated Carbon Monoxide Containing Atmosphere of Biomass-to-Liquid Plants

Abstract: Biomass fuel is effective renewable energy and being used for replacing fossil fuel energy. It can be produced from synthesis gas containing a high percentage of carbon monoxide (CO) and hydrogen (H2) in biomass-to-liquid plants. Austenitic stainless steel AISI 316L (Cr17% Ni 10% Mo 2%) is used for equipment parts in chemical and petrochemical industries due to good corrosion resistance at various operating conditions. The corrosion resistance of stainless steel may be degraded by the reduction reaction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Marián Vach et al [21] reported that the second phase particles, such as M23C6, can be found in the austenitic stainless steel and the presence of those particles resulted in increased hardness. Treewiriyakitja et al [22] found the formation of carbide particles resulted in the degraded corrosion resistance of austenitic stainless steel. In this experiment, microstructural analysis in Fig.…”
Section: Anti-corrosion Performance Alternation Observationmentioning
confidence: 99%
“…Marián Vach et al [21] reported that the second phase particles, such as M23C6, can be found in the austenitic stainless steel and the presence of those particles resulted in increased hardness. Treewiriyakitja et al [22] found the formation of carbide particles resulted in the degraded corrosion resistance of austenitic stainless steel. In this experiment, microstructural analysis in Fig.…”
Section: Anti-corrosion Performance Alternation Observationmentioning
confidence: 99%
“…Using ferritic stainless steel at high temperatures is one possible way to reduce material costs for general stainless-steel components under low aggressive environments in power plants. However, intergranular corrosion and deterioration of passive film may present during the combustion process due to carbon diffusion [9][10][11]. Solid carbon from soot particles can diffuse into austenite grain at temperatures between 830℃ to 1400℃ and form chromium carbide along grain boundaries following Equation (1-3) [5,12,13].…”
Section: Introductionmentioning
confidence: 99%